O współpracy zespołu Pracowni Filologii Białoruskiej IS PAN z prof. Władysławem Kuraszkiewiczem w zakresie badania gwar - Kondratiuk, Michał (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2018)
The article shows the role of Prof. Władysław Kuraszkiewicz in creating and developing Byelorussian investigations in Poland after World War II. In the interwar period he investigated Russian dialects in Podlasie, Polesie and Helm Regions. In 1937 he was the first to collect rich dialectae materials in 70 villages between the Bug and the Narew Rivers, which he published in 1939 The Outline of east-slavonic dialectology with examples of dialectal texts, and edition, Warsaw 1963, made him famous. Prof. Kuraszkiewicz was the reviewer of the first three volumes of the Atlas of East Slavonic Dialects of Bialystok Region (Wrocław 1980–1993). Before 1985 he initiated the investigations of the Atlas of East Slavonic Dialects of the Bug River Region, carried out by to teams: the Institute of Slavistic Studies in Warsaw and the Institute of Slavistic Studies UMCS in Lublin. He also contributed to the development of scientific personnel. He promoted and reviewed the doctor`s and assistant-professor research. He supported the development of Byelorussian studies and set up “International Association of Byelorussists and Polish Byelorussists Society”.